Evaluation of mycoparasitic Trichoderma atroviride and entomopathogenic Aspergillus niger as potential bioinsecticides against the dengue vector, Aedes aegypti - Banduwardena, A. V. Ranthilini C.; Mendis, B. Anushka N.; Thambugala, Kasun M.; Fernando, H. Sachini D.; Promputtha, Itthayakorn (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionOver the past three decades, dengue disease incidence has significantly increased worldwide, creating serious public health concerns. The principal mosquito vector, Aedes aegypti, exhibits resistance to commonly used insecticides, reducing the efficacy of vector control measures. Thus, the necessity for alternate strategies is critical. Using bioinsecticides such as entomopathogenic fungi (EPF) is one such strategy. This study details the evaluation of mycoparasitic Trichoderma atroviride and entomopathogenic Aspergillus niger against pyrethroid-resistant and pyrethroid-susceptible Ae. aegypti populations.Materials and methodsMolecular identification of the isolated entomopathogenic fungal strains was done using ITS-rDNA sequence data. Larvicidal and adulticidal assays were performed using different spore concentrations of fungal species. Pupal emergence was assessed from the survived larvae of larvicidal assays.ResultsLarvicidal assays revealed the highest mortality of 60% for T. atroviride after 9 days of exposure when compared with the highest mortality of 52% for A. niger after 6 days of exposure. No significant difference was observed between the pyrethroid-resistant and pyrethroid-susceptible mosquito colonies, suggesting a lack of connection between prior resistance status and EPF pathogenicity. No pupal mortality was observed, although pupal duration was prolonged. Both EPF strains exhibited 100% mortality in adulticidal assays, signifying the potential use of the two fungal species as adulticides.ConclusionHowever, further studies are needed to understand the biology of EPF, its mechanism of action, the mosquito immune pathways activated, and the effect on non-target organisms. The findings have implications for the possible use of A. niger and T. atroviride as potential bioinsecticides against the control of Ae. aegypti.